Formation of winter rye productivity and grain quality under insufficient moisture - D. D. Saifutdinova; M. L. Ponomareva; L. V. Ilalova (Зерновое хозяйство России)
The purpose of the current work was to identify the features of the formation of productivity and grain quality indicators of modern winter rye varieties and hybrids, depending on the moisture content of the spring-summer vegetation period. The study was carried out at the TatRIA FRC KazSC RAS (Republic of Tatarstan) in contrasting weather years (2020–2021). The object of the study was the population of winter rye varieties ‘Estafeta Tatarstana’, ‘Radon’, ‘Ogonyok’, ‘Tantana’, ‘Podarok’, ‘Zilant’ and German heterotic hybrids ‘KVS Aviator’ and ‘KVS Prommo’. There has been established that for the studied rye varieties and hybrids, grain productivity decrease caused by drought was 44 %, number of heads per 1 m2 reduced on 19.4 %, and 1000-grain weight dropped on 27.7 %. The advantages of rye hybrids according to grain productivity with a good supply of spring-summer vegetation were 14 %, with a lack of moisture they were 10 %. Among the population varieties, the varieties ‘Zilant’, ‘Podarok’ and ‘Tantana’ had the least losses from drought. There has been identified that in terms of baking and technological qualities the situation was vice versa. In a dry year, there was an increase of such indicators as the amylogram height (in 2 times), protein (on 20.8 %), and falling number (on 14.2 %). There has been established that the biochemical parameters of grain (content of fiber, ash, oil) improved significantly. The obtained study results have indicated that in dry years it is necessary to prepare batches of rye with high technological qualities and biochemical properties for baking industry.